Systematic and functional analysis of non-specific lipid transfer protein family genes in sugarcane under Xanthomonas albilineans infection and salicylic acid treatment - Li, Juan; Zhao, Jian-Ying; Shi, Yang; Fu, Hua-Ying; Huang, Mei-Ting; Meng, Jian-Yu; Gao, San-Ji (Frontiers in Plant Science, 2022)
Plant non-specific lipid transfer proteins (nsLTPs) are encoded by small basic proteins, playing a significant role in regulating a wide range of physiological processes. To date, no genome-wide survey and expression analysis were performed for this gene family in sugarcane. Therefore, in this study we identified the nsLTP gene family in S. spontaneum and characterized expression profiling of nsLTPs in two sugarcane cultivars with contrasting resistance to leaf scald in response to infection by Xanthomonas albilineans (Xa) as well as exogenous salicylic acid (SA) treatment. A total of 71 SsnsLTP genes including 66 alleles were identified in S. spontaneum AP85-441 at genomic level. Tandem (9 gene pairs) and segmental (36 gene pairs) duplication events contributed to the expansion of SsnsLTP gene family. Transcriptome analysis showed 29.6% (21/71) SstnsLTP genes had tissue-specific expression especially in stem tissue at early seedling stage. Five SstnsLTP proteins were predicted to interact with five other gene proteins. ShnsLTPI.8/10/Gb.1 genes were significantly upregulated in LCP85-384 (resistant cultivar) but downregulated in ROC20 (susceptible cultivar), suggesting that they play a positive regulatory role in sugarcane in response to Xa infection. Conversely, ShnsLTPGa.4/Ge.3 along with an interacting protein gene (3-ketoacyl-CoA synthase 10, KCS10) would act as a negative regulator responding to this bacterium infection. Moreover, 11 ShnsLTPs and five interacted protein genes were positively induced in LCP85-384 at 24 h post exogenous SA treatment. In conclusion, our results provide valuable information towards elucidating the function of ShnsLTP family members under Xa infection and SA stress and supply with novel gene sources for developing sugarcane resistant to bacterial pathogen stimuli.